TINDAK UJAR DIREKTIF DALAM FILM THE HOBBIT: BATTLE OF THE FIVE ARMIES (Suatu Analisis Pragmatik) - Tembengi, Handry (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled â€œDirective Act in film The Hobbit: Battle of the Five Armiesâ€. It is a pragmatic analysis that focuses on one kind of Illocutionary act, called directive act. It is an attempt to find the functions of directive act in the film. The data have been taken from the characterâ€™s utterances in the film The Hobbit. The writer analyzed the data descriptively by concentrating on utterances which contain directive act. The theory used in this research is taken from Searleâ€™s theory about illocutionary act especially in directive act. The findings of this research showed several functions of directive act in film The Hobbit: Battle of the Five Armies. The functions of directive act in film The Hobbit: Battle of the Five Armies can be classified into five functions those are commanding, suggesting, requesting, demanding, and ordering. Â  Keywords: Directive act, Functions, The Hobbit: Battle of the Five Armies